STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA TENAGA ADMNINISTRASI UNTUK MENCIPTAKAN SISTEM ADMINISTRASI SEKOLAH YANG EFEKTIF DI SMA NEGERI 1 SELESAI - Seppiani; Hamidah Darma; Lendra Faqrurrowzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the principals strategy in improving the performance of administrative staff to create an effective school administration system. This research employs a qualitative method with descriptive data presentation. The data sources used by the researcher include person, place, and paper. Data collection techniques consist of interviews, observations, and documentation. The data analysis techniques applied are data reduction, data presentation, and conclusion drawing or verification. The results of the study indicate that, as a leader, the school principal must have strategies to enhance the performance of administrative staff. The principals strategies serve as the foundation for empowering administrative staff performance so that school administrative activities can run effectively. The strategies implemented by the principal at SMA Negeri 1 Selesai generally include four main aspects: providing motivation, communication, skill training, and guidance. The role of administrative staff in creating an effective and efficient school administration system is carried out through student data management, curriculum management, and maintaining good communication with various parties.